2017
DOI: 10.1167/iovs.16-20717
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles of Tear Fluid From Patients With Pediatric Lacrimal Duct Obstruction

Abstract: PURPOSE. This study evaluated the cytokine levels in unilateral tear samples from both sides in patients with pediatric lacrimal duct obstruction.METHODS. Fifteen cases of unilateral lacrimal duct obstruction (mean, 26.9 6 28.7 months old) were enrolled in this study. Tear samples were collected separately from the obstructed side and the intact side in each case before surgery, which was performed under general anesthesia or sedation. The levels of IL-2, IL-4, IL-6, IL-10, TNF, IFN-c, and IL-17A then were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[7][8][9] Patients with lacrimal drainage pathway diseases exhibit elevated levels of various in ammatory cytokines in tear uid. [16][17][18] Recanalization of the lacrimal drainage pathway may reduce the levels of interleukins and matrix metalloproteinases. Therefore, treatment of the lacrimal drainage pathway is necessary for the treatment of corneal epitheliopathy in lacrimal duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Patients with lacrimal drainage pathway diseases exhibit elevated levels of various in ammatory cytokines in tear uid. [16][17][18] Recanalization of the lacrimal drainage pathway may reduce the levels of interleukins and matrix metalloproteinases. Therefore, treatment of the lacrimal drainage pathway is necessary for the treatment of corneal epitheliopathy in lacrimal duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is thought to be a pathology of NLDO, and it has been reported that several inflammatory cytokines, such as IL-2, IL-6, IL-10, vascular endothelial growth factor, and fibroblast growth factor 2, are increased in the tear fluid of patients with PANDO 2 , and that IL-6, specifically, is increased in the tear fluid of patients with CNLDO 3 . As the findings in several previous reports have suggested that IL-6 attenuates the barrier function between cells 7,8 , our results revealed that IL-6 induced barrier dysfunction of cultured LDECs.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that various tear cytokines, such as interleukin (IL)-2, IL-6, and IL-10, are involved in the pathology of primary acquired nasolacrimal duct obstruction (PANDO) 2 , and that IL-6 is also involved in congenital NLDO (CNLDO) 3 . Thus, the suppression of the level of inflammatory cytokines in tears is considered to be a key factor in the development of new methods for the treatment of NLDO.…”
Section: Rebamipide Promotes Lacrimal Duct Epithelial Cell Survival Vmentioning
confidence: 99%
“…Two main methods were employed to collect tears, capillary pipettes and Schirmer method 2 , 3 . Schirmer method was chosen as this is safe, convenient and is known to cause less irritation 4 . Tears remain in the conjunctival fornix, and we don’t think the strip which was put in the fornix would have caused any contamination.…”
mentioning
confidence: 99%